Feeding behavior of banana and taro aphids (Pentalonia spp.) (Hemiptera: Aphididae) on musaceae and araceae plants: an electrical penetration graph (dc-epg) study - Purnama Hidayat; Siti Rahmah; Yuni Apriliana; Nina Maryana; Alan Soffan; Sri Hendrastuti Hidayat (Penerbit Universiti Kebangsaan Malaysia, 2024)
The feeding behavior of the banana aphid, Pentalonia nigronervosa Coquerel, and the taro aphid, P. caladii van der Goot (Hemiptera: Aphididae), was evaluated on plants from the Musaceae family (bananas cv. Kepok [Musa x paradisiaca], and cv. Mas [M. acuminata]) and the Araceae family (taro [Colocasia esculenta], and dumb cane [Dieffenbachia sp.]) using the electrical penetration graph (DC-EPG) technique. These two aphids are reported as vectors of Banana bunchy top virus (BBTV), which causes banana bunchy top disease (BBTD). In the laboratory, the EPG equipment setup involved attaching the aphids to the host plants using a fine gold wire connected to an EPG box for signal amplification. This setup was linked to a PC for waveform recording using EPG Stylet 3.0 software for 10 hours. Specific EPG recording parameters were selected for data analysis. The results suggest that the banana aphid grows better on banana plants (Musaceae) and less on plants from the Araceae family, whereas the taro aphid prefers taro and similar plants (Araceae) over banana plants (Musaceae). This also indicates that the taro aphid is less likely to spread BBTV on bananas than the banana aphid.